KARAKTERISTIK KIMIAWI DAN AKTIVITAS ANTIOKSIDAN DAUN KERSEN (Muntingia calabura) PADA KETINGGIAN WILAYAH YANG BERBEDA - Ade Galuh Rakhmadevi; Maria 'Azizah; Anna Mardiana Handayani (JURNAL AGROTEKNOLOGI, 2021)
Kersen trees (Muntingia calabura L.) are included in the Elaeocarpaceae family and are mostly used as a protective tree. The kersen leaves were an environmental waste (trash) and still lacks implementation in food processing. This study was aimed to determine the chemical characteristics and antioxidant activity of kersen leaves at different altitudes and their potential as an herbal tea. The difference in the height of the place to grow will be used as a factor to be studied so that this study uses a completely randomized design with a one factor pattern (height the place of growings). Kersen leaves were taken from three districts, namely Jember (83 amsl/above mean sea level), Situbondo (5 amsl), and Bondowoso (255 amsl). The results showed that the chemical characteristics of kersen leaves consisting of moisture content, ash content, fat content, and carbohydrate content were not significantly different between regions, while protein content and antioxidant activity levels were significantly different between regions. Keywords: antioxidant activities, kersen leaves